PEMANFAATAN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS). APAKAH TERDAPAT HUBUNGAN AKSES PELAYANAN DAN DUKUNGAN KELUARGA? - Aipipidely, Diana; Puspitasari, Mulidiah; Dahmar, Dahmar; Aryatika, Karera (Ensiklopedia of Journal, 2025)
Noncommunicable diseases (NCDs) are a group of chronic diseases that are not transmitted from one individual to another. The onset of these diseases is gradual and progressive. The increase in the incidence of noncommunicable diseases (NCDs) globally is not only seen in cases of diabetes mellitus, but also in hypertension, which is one of the chronic and progressive NCDs. The purpose of this study was to determine the relationship between access to services and family support with the utilization of chronic disease management programs (prolanis). The research design used in this study was cross-sectional. The study was conducted in the working area of the Gattareng Community Health Center. The study was conducted in October 2024. The population consisted of all BPJS Health participants with chronic diseases (diabetes mellitus and hypertension) in the Gattareng Community Health Center working area. The sample consisted of 205 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between access to services (p value: 0.04) and family support (p value: 0.00) with the utilization of Prolanis services. It is recommended that the Community Health Center increase its efforts to provide information and benefits regarding Prolanis services not only to patients but also to their family members. Keywords: Access, Family Support, Prolanis